Síntese e Determinação da Estrutura do Complexo NI(II)(L-TREONINA)2(H2O)2 por Difração de raios - X em Monocristais - Melo, Ezequiel Borges (2015)
Amino acids, having both the carboxylic group and amine group, may act as bidentate ligands and, depending on its radical group can also act as tridentate ligands. Amino acids complexed with transition metals have attracted the interest of chemists and physicists because of its possible applications and physical properties. L-threonine complexes with Cu+2 (Cu(II)(L-Threonine)2(H2O)), Co+2 (Co(II)(L-Threonine)2(H2O)2) e Zn+2 (Zn(II)(L-Threonine)2(H2O)2) transition metals already exist in the literature and their crystalline structures are different. However, L-threonine complexed with Ni+2 was not found in the literature. Thus, in this study, we used the amino acid L-threonine as a ligand and Ni+2 ion as the transition metal to obtain the crystal of L-threonine complexed with Ni. For that we used the Slow Evaporation crystal growth method, where a solution containing L-threonine and NiCl2.6H2O with molar ratio (2:1) and NaOH to get a basic pH, is allowed to stand for promoting the crystal growth. To get the crystal structure of this material, X-ray diffraction measures were carried in a APEX2 DUO diffractometer of the Crystallography Laboratory in the Physics Institute of UFG. The data analysis and the resolution of the structure were performed the package Bruker SHELXTL and also using the mechanism of structural determination by Direct Methods, one of the most used ways to overcome the phase problem in the structure determination of small molecules. L-threonine complexed with Ni has the chemical formula Ni(II)(L-Treonina)2(H2O)2 and crystallizes in the orthorhombic system with space group C2221. Thus, we identified that the Ni(II)(L-Treonina)2(H2O)2 crystal has a very similar crystalline structure as Co(II)(L-Treonina)2(H2O)2. Furthermore, the knowledge of the structure of this material opens up a range studies can be performed on it.